2021
DOI: 10.1111/apt.16361
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcome after anti‐tumour necrosis factor therapy discontinuation in 1000 patients with inflammatory bowel disease: the EVODIS long‐term study

Abstract: Summary Background The long‐term outcome of patients after antitumour necrosis factor alpha (anti‐TNF) discontinuation is not well known. Aims To assess the risk of relapse in the long‐term after anti‐TNF discontinuation. Methods This was an extension of the evolution after anti‐TNF discontinuation in patients with inflammatory bowel disease (EVODIS) study (Crohn's disease or ulcerative colitis patients treated with anti‐TNFs in whom these drugs were withdrawn after achieving clinical remission) based in the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 25 publications
1
13
0
1
Order By: Relevance
“…There is a substantial heterogeneity among these studies. The majority of these studies examined relapse rates in patients with clinical remission [ 9 , 10 , 17 , 18 , 20 , 25 27 ]. However, the applied definitions of clinical remission vary strongly.…”
Section: Discussionmentioning
confidence: 99%
“…There is a substantial heterogeneity among these studies. The majority of these studies examined relapse rates in patients with clinical remission [ 9 , 10 , 17 , 18 , 20 , 25 27 ]. However, the applied definitions of clinical remission vary strongly.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review and meta-analysis of previous observational studies demonstrated that 28% of UC and 36% of CD patients relapsed at 12 months following discontinuation of anti-TNF agents [ 8 ]. In addition, a recent large retrospective observational study evaluated >1,000 IBD patients who discontinued IFX or ADA and revealed that 12% of patients relapsed annually, with a cumulative relapse rate of 48% in 5 years after discontinuation [ 31 ].…”
Section: Discontinuation Of Tnfimentioning
confidence: 99%
“…39 In addition, a recent large-scale retrospective observational study of 1,000 IBD patients who discontinued infliximab or adalimumab demonstrated that 12% of patients relapsed annually, and the cumulative relapse rate at years was 48% after discontinuation. 40…”
Section: Anti-tnf-α 1) Discontinuation Of Tnfimentioning
confidence: 99%
“…38 A large-scale observational study also showed that 60% of patients who relapsed after discontinuation were treated with the same TNFi, in which 73% of patients achieved remission. 40 However, decisions on whether the same TNFi should be used were made by physicians or patients in clinical practice; therefore, the outcome might have been biased.…”
Section: Tnfimentioning
confidence: 99%
See 1 more Smart Citation